Cooperative relative navigation for multi‐UAV systems by exploiting GNSS and peer‐to‐peer ranging measurements. Issue 1 (23rd December 2020) - Shen, Jiawen; Wang, Shizhuang; Zhai, Yawei; Zhan, Xingqun
Abstract: Multiple unmanned aerial vehicle (UAV) systems have attracted extensive research interest for their potential benefits of scalability and flexibility. To keep all the UAVs in the desired formation, the navigation system must continuously provide highly accurate and robust relative positioning results. In open‐sky areas, this mission can be achieved using Global Satellite Navigation System (GNSS). However, the performance will be significantly degraded in urban canyons, due to signal blockage or high multipath. In response, we propose a cooperative relative navigation method that exploits peer‐to‐peer (P2P) ranging measurements to assist GNSS, and introduce cooperative technology to relative navigation. The principle of this approach is integrating multiple observations from multiple sensors and vehicles in the formation, thereby (a) improves navigation accuracy and (b) enhances the robustness against operational scenario changes. Simulations and flight experiments are carried out to validate the proposed algorithm in urban environments, and the results reveal significant accuracy improvement comparing to GNSS only. In addition, multiple sets of sensitivity analyses are performed to address the impact of UAV numbers, formation geometry and accuracy of P2P ranging on navigation performance.